Enhancement of Biosugar Production Via Enzymatic Yydrolysis of Sodium Hydroxide Pretreated Oil Palm Bagasse: A Statistical Perspective - Aina Fauzi, Nurul; Harun, Shuhaida; Md Jahim, Jamaliah; Ping Tan, Jian (International Journal of Engineering and Technology, 2019)
Oil palm frond bagasse (OPFB) is the major agriculture waste from the production of palm oil with 0.66g/g of total carbohydrate to serve as potential carbon source for downstream processing in producing succinic acid. This study focused in determining the optimum process variable conditions for the 1% glucan loading for enzymatic hydrolysis process with commercial blending cellulase enzyme mixture of Cellic CTec 2 and hemicellulase enzyme of Cellic HTec 2. Using statistical approach of Response Surface Methodology, three independent process variables; specific enzyme activity (5 - 80 FPU/g glucan), hydrolysis temperature (30 - 70 °C), and agitation speed (100 - 180 rpm) were investigated at five different levels (-α,-1, 0, +1, +α). The regression models indicated that R2 for glucan conversion at 1% GL enzymatic hydrolysis was 97.2% showing the experimental variations were well-defined by the models. For the lack of fit test, the p-values > 0.05 proves that the model was significant to the prediction model. While both specific enzyme activity and hydrolysis temperature were statistically significant, there was no interaction observed between these variables. Although experimental runs reported the maximum glucan conversion of 94% was achieved in the 1% GL hydrolysis with 83.75 FPU/g glucan and 50°C after 96 hours of saccharification process, through validation process, the optimum conditions were determined at 30 FPU/g glucan, 45oC and 100 rpm respectively where these saccharification conditions achieved 90% glucan conversion within 72 hours.